Analysis of specialists’ shortages in schools with inclusive education in Kazakhstan - Yussupova, D.Sh.; Zhussipbek, T.Z.; Dwyer, H. («Академик Е.А. Бөкетов атындағы Қарағанды университеті» КЕАҚ баспасы, 2023)
Object: to reveal the causes behind staff shortage and staffs drain of support specialists (psychologists, special teachers, speech therapists) in general schools with inclusive education. Methods: qualitative study with the utilization of semi-structured interviews and thematic analysis of the data; SWOT analysis for support specialists’ availability in general schools. Findings. The findings indicate that the major reasons behind the staff shortage and turnover come along with dissatisfaction of teachers with working conditions as low salaries and heavy workload, lack of qualifications and availability of specialists and the organizational conditions such as administrative support and decision-making input in school settings. SWOT analysis provides an overall observation for the provision of support specialists and their scarcity in schools. Conclusions: Based on the analyses, the study concludes that sufficient salaries, adequate workload, professional competence and administration support mostly determine staff will continue their functions in teacher position.
Қазақстандағы инклюзивті білім беретін мектептердегі мамандардың жетіспеушілігін талдау
Анализ нехватки специалистов в школах с инклюзивным образованием в Казахстане
Keywords: inclusive education; staff shortage; staff drain; support specialists